Türk Sigorta Sektörü Hayat ve Emeklilik Şirketlerinin Etkinlik Analizi - (:unkn) unknown (My University, 2010)
0

The Insurance Industry, which is an important component of the servi- ce industry, has not had a considerable influence in the Turkish Finance Industry. The importance of the insurance industry can be raised to the level of developing countries by improving their performance. Performance analyses evaluate units by using the concepts of efficiency and productivity as instruments. This study examines the life and life/pension fund companies' productivity by input oriented data envelopment analysis between 2004-2008. The ranking of the companies is determined and evaluated by considering the efficiency figures in the above-mentioned period. Furthermore, while it is con- cluded that the average efficiency value of the industry is high and has a homogeneous structure, it is determined that the changes faced by companies after mergers or acquisitions affect the efficiency values positively except the first year.
Efficiency analysis of life and life/Pension companies in Turkish insurance sector
Keywords: Tarih